2011
DOI: 10.1021/nl200993g
|View full text |Cite
|
Sign up to set email alerts
|

ALD Functionalized Nanoporous Gold: Thermal Stability, Mechanical Properties, and Catalytic Activity

Abstract: Nanoporous metals have many technologically promising applications, but their tendency to coarsen limits their long-term stability and excludes high temperature applications. Here, we demonstrate that atomic layer deposition (ALD) can be used to stabilize and functionalize nanoporous metals. Specifically, we studied the effect of nanometer-thick alumina and titania ALD films on thermal stability, mechanical properties, and catalytic activity of nanoporous gold (np-Au). Our results demonstrate that even only 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
205
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(213 citation statements)
references
References 52 publications
7
205
1
Order By: Relevance
“…Biener et al noted that adsorbed oxygen from ozone decomposition helps to stabilize the nanostructure against coarsening at low temperatures [115]. More recently, atomic layer deposition was used to form a very thin layer of Al 2 O 3 or TiO 2 on nanoporous gold, which helped to suppress coarsening and improve thermal stability [116].…”
Section: Specific Features Of Nanoporous Goldmentioning
confidence: 99%
“…Biener et al noted that adsorbed oxygen from ozone decomposition helps to stabilize the nanostructure against coarsening at low temperatures [115]. More recently, atomic layer deposition was used to form a very thin layer of Al 2 O 3 or TiO 2 on nanoporous gold, which helped to suppress coarsening and improve thermal stability [116].…”
Section: Specific Features Of Nanoporous Goldmentioning
confidence: 99%
“…In fact, the oxide growth behavior is also affected with the choice of precursors, Biener and coworkers reported that using TiCl 4 and H 2 O to grow TiO 2 films with 10 cycles on Au tended to form continuous and smooth coatings. 87 The continuous coating completely encapsulated the Au surfaces resulted in the rapid disappearing of activity in CO oxidation. The differences between two kinds of growth modes could be attributed from the initial nucleation differences of two Ti precursors.…”
Section: B Selective Passivation Of Edge/low-coordinated Sitesmentioning
confidence: 99%
“…In recent years, many biological functions of materials were prepared by surface modification and widely used in medicine [1][2][3][4][5][6][7][8], biology and other fields, especially in the separation of various proteins [9][10]. Protein is an important component of all living organisms, and it is the material basis of all life.…”
Section: Introductionmentioning
confidence: 99%